Implementation of the Teams Games Tournament (TGT) Learning Model in Pancasila Education Subjects for Grade IV Students - Danielle R Gaikwad; Deva Riana Ramadhani; Prissy Aura Aisyah; Dewi Mutia Safitri; Ifma Hijriyani; Agung Setyawan (Journal of Action Research in Education, 2026)
This research aims to improve students' cognitive learning outcomes in the Pancasila Education learning subject by using the Teams Games Tournament (TGT) learning model in grade IV students of SDN TANJUNG 1. The problem found is that students are less involved and less enthusiastic in learning so that the learning process is less effective. This research is a class action research which is carried out in two cycles. Each cycle consists of the stages of planning, implementation of actions, observation, and reflection. The research was carried out at SDN TANJUNG 1 with the research subject, namely grade 4 students totaling 12 students. This research method uses a quantitative method. Data collection techniques include observation, interviews, tests, and documentation. The research instrument is in the form of observation sheets of teacher and student activities, as well as learning outcome test questions. Data analysis techniques use data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that the use of the TGT learning model can improve students' cognitive learning outcomes. In cycle I, the number of students who completed their studies reached an average of 68.8, increasing to 89.1 in cycle II. The conclusion of this study is that the TGT learning model is effective in improving the cognitive learning outcomes of grade IV students in Pancasila Education learning subjects. It is recommended to teachers to use the TGT learning model as an alternative in learning Pancasila Education to increase student activity and learning outcomes.